PENINGKATAN HASIL BELAJAR PERPANGKATAN DAN AKAR SEDERHANA MELALUI PENERAPAN ALAT PERAGA ‘PAPER DAN NOKRUMTUL’ PADA PESERTA DIDIK KELAS V DI SD NEGERI 2 BENGKULU SELATAN - Zarlan Saryadi (PAKAR Pendidikan, 2018)
The purpose of this classroom action research is to: (1) describe mathematics learning in simple matter of powers and roots in grade V elementary school students of State 2 South Bengkulu by applying 'Paper and Nokrumtul' props; and (2) to describe the effectiveness of the Implementation of 'Paper and Nokrumtul' Toolkit on Improving Learning Outcomes of Simple Departments and Roots to Grade V Students in elementary school students of State 2 South Bengkulu. The location of this class action research activity is at elementary school State number 2 South Bengkulu. Students who are the subject of this study are students in class V with the number of 20 people consisting of 12 men of gender and 8 others came from the female sex, all students as subjects of this study will be subject to action in accordance with the flow real learning. From the results of learning activities that have been done for two cycles, and based on all the discussion and analysis that has been done can be concluded that the learning by applying the props "Paper and Nokrumtul" has a positive impact in improving student learning outcomes in class V elementary school students of State 2 South Bengkulu which is marked by the improvement of student learning outcomes in each cycle, the average value of student learning outcomes reached 78.75 with 80% learning completeness in cycle I and average learning outcomes reached 86.25 with 100% complete learning in cycle II . Implementation of learning with props "Paper and Nokrumtul" in the math lessons also have a positive influence, which can increase the motivation of students. Thus the application of learning through props "Paper and Nokrumtul" proved effective to improve learning outcomes of students.